Prutor: An Intelligent Learning and Management System for Programming Courses. - KARKARE, AMEY; KAR, PURUSHOTTAM (Communications of the ACM, 2022)
The article discusses the use of the artificial intelligence (AI), browser-based tutoring system known as Prutor for use in university computer programming, or coding, courses in India. The role that Prutor plays in automating tasks typically done by teachers' assistants (TAs), including in regard to lessening their workload, is discussed.